(untitled) (Research, Society and Development, 2022)
The objective of this study was to identify the occurrence and characteristics of occupational accidents with exposure to biological material among nursing workers at a clinic hospital. This is an exploratory research, with a quantitative approach and cross-sectional design, carried out in a university clinic hospital in Minas Gerais from 2008 to 2009. For data collection, an anonymous and self-administered instrument was developed. Data analysis was performed using descriptive and association statistics. Of the 322 professionals studied, 79 suffered accidents involving biological material, and nursing technicians (72.15%) were the most exposed, the main contaminating agent was blood (77.21%) during venipuncture procedures (35.4%) and the highest prevalence of accidents was observed in the afternoon shift. The high prevalence of work-related accidents with biological material in the nursing team was related to the long daily work hours, the overconfidence shown by the more experienced professionals and the non-adherence to biosafety standards.